Why Do Sellers (Usually) Prefer Auctions? - Bulow, J; Klemperer, P (American Economic Association, 2009)
We compare the most common methods for selling a company or other asset when participation is costly: a simple simultaneous auction, and a sequential process in which potential buyers decide in turn whether or not to enter the bidding. The sequential process is always more efficient. But pre-emptive bids transfer surplus from the seller to buyers. Because the auction is more conducive to entry - precisely because of its inefficiency - it usually generates higher expected revenue. We also discuss the effects of lock-ups, matching rights, break-up fees (as in takeover battles), entry subsidies, etc.